Dose dependent effects of nitrate supplementation on cardiovascular control and microvascular oxygenation dynamics in healthy rats - Ferguson, Scott K.; Hirai, Daniel M.; Copp, Steven W.; Holdsworth, Clark T.; Allen, Jason D.; Jones, Andrew M.; Musch, Timothy I.; Poole, David C. (My University, 2014)
High dose nitrate (NO3−) supplementation via beetroot juice (BR, 1 mmol/kg/day) lowers mean arterial blood pressure (MAP) and improves skeletal muscle blood flow and O2 delivery/utilization matching thereby raising microvascular O2 pressure (PO2mv). We tested the hypothesis that a low dose of NO3− supplementation, consistent with a diet containing NO3− rich vegetables (BRLD, 0.3 mmol/kg/day), would be sufficient to cause these effects. Male Sprague–Dawley rats were administered a low dose of NO3− (0.3 mmol/kg/day; n = 12), a high dose (1 mmol/kg/day; BRHD, n = 6) or tap water (control, n = 10) for 5 days. MAP, heart rate (HR), blood flow (radiolabeled microspheres) and vascular conductance (VC) were measured during submaximal treadmill exercise (20 m/min, 5% grade, equivalent to ∼60% of maximal O2 uptake). Subsequently, PO2mv (phosphorescence quenching) was measured at rest and during 180 s of electrically-induced twitch contractions (1 Hz, ∼6 V) of the surgically-exposed spinotrapezius muscle. BRLD and BRHD lowered resting (control: 139 ± 4, BRLD: 124 ± 5, BRHD: 128 ± 9 mmHg, P < 0.05, BRLD vs. control) and exercising (control: 138 ± 3, BRLD: 126 ± 4, BRHD: 125 ± 5 mmHg, P < 0.05) MAP to a similar extent. For BRLD this effect occurred in the absence of altered exercising hindlimb muscle(s) blood flow or spinotrapezius PO2mv (rest and across the transient response at the onset of contractions, all P > 0.05), each of which increased significantly for the BRHD condition (all P < 0.05). Whereas BRHD slowed the PO2mv kinetics significantly (i.e., >mean response time, MRT; control: 16.6 ± 2.1, BRHD: 23.3 ± 4.7 s) following the onset of contractions compared to control, in the BRLD group this effect did not reach statistical significance (BRLD: 20.9 ± 1.9 s, P = 0.14). These data demonstrate that while low dose NO3− supplementation lowers MAP during exercise it does so in the absence of augmented muscle blood flow, VC and PO2mv; all of which are elevated at a higher dose. Thus, in healthy animals, a high dose of NO3− supplementation seems necessary to elicit significant changes in exercising skeletal muscle O2 delivery/utilization.
Keywords: Nitric oxide; Exercise; Dietary nitrate; Nitrite; Mean arterial pressure; Blood flow